A COMPARISON OF GENE CO-NETWORKS REVEALED THE MOLECULAR MECHANISMS OF FLORAL TRANSITION AND INFLORESCENCE DEVELOPMENT IN BARLEY (HORDEUM VULGARE L.) - C. Mao; 2#; D. Kong; 2# L. Wang; H. Wang; H. Zhang; J. Xu; 3; Y. Shen; 3 (Journal of Animal and Plant Sciences, 2020)
Inflorescence development and flower organ development are important events in plant development, directly affecting sexual reproduction and plant yield. The molecular mechanism of the inflorescence development in barley (Hordeum vulgare L.) has rarely been studied. In order to mine the genes involved in the development of barley inflorescence, published RNA-seq data were analyzed by weighted gene co-expression network analysis (WGCNA), and six modules were identified. Further analysis showed that three modules (green, light green and purple) were significantly associated with the stage during floral development. The module-specific genes were enriched in physiological processes such as transporter activity, metal binding and oxidoreductase activity. In barley, the genes encoding the MADS-box transcription factor family protein, REDUCED VERNALIZATION RESPONSE1 (VRN1) and ASYMMETRIC LEAVES1 were identified as hub genes in the corresponding modules, and were reported previously to be connected with vegetative apices, leaf growth and auxin signaling. In addition, we also found candidate genes encoding AP2/B3-like transcriptional factor family protein, proline-rich family protein, growth-regulating factor 2 (GRF2), armadillo-repeat containing protein (ARP), xyloglucan endotransglucosylase/hydrolase 9 (XTH9) and G2484-1. This work discovered candidate genes that highly related to the inflorescence development in barley using the constructed genetic network relationship, and provided new ideas and datasets for studying the molecular mechanism of barley inflorescence development.
Keywords: Barley; Co-expression network analysis; Inflorescence development; Transcriptomics